344 views
0 votes
If 3p-q=6 and 2p+3q=4 find q

2 Answers

2 votes

Answer:

Correct Answer: Option A

Explanation

3p - q = 6 ........ 1

2p + 3q = 4 ....... 2

Multiply eqn 1 by 3

9p - 3q = 18 ........ 3

2p - 3q = 4 ......... 2

Add eqn3 and eqn2

11p = 22 => p = 22/11 = 2

Substitute for p =2 in eqn1

3p - q = 6

3x2 - q = 6 => 6 - q = 6 => -q = 6 - 6

q = 0

Explanation:

User Lowrin
by
5.0k points
0 votes

Answer:

It is -24/11

Explanation:

This is a system of equations. Using substitution should give the answer.

Taking the first equation, q = 3p - 6. Plug this into the second equation.

2p + 3(3p - 6) = 4. Distributing gives 2p+ 9p - 18 = 4. Subtract 4 from both sides to give: 11p - 14 = 0. p = 14/11

Plug this back into the first equation.

42/11 - q = 6

q = 42/11 - 6, which equals -24/11

Hope this helps!

User Cenoc
by
5.0k points